Kompetensi Pedagogik Guru dalam Mengelola Pembelajaran IPA di SD dan MI - Indriani, Fitri (LP2M IAIN Samarinda, 2015)
The objective of this study was to know the teachersâ€™ pedagogic competence to manage the teaching and learning of IPA at SD Negeri Tamansari 1 Kota Yogyakarta and MIN Kota Yogyakarta II. The research methods of the study is descriptive qualitative. Data were collected through observation, interview, and documentation. Data were validated by using triangulation. Data were analyzed descriptively. The result of data findings shows that the teachersâ€™ pedagogic competence to manage the teaching and learning of IPA at SD Negeri Tamansari 1 Kota Yogyakarta is categorized â€œgoodâ€. Meanwhile, the teachersâ€™ pedagogic competence to manage the teaching and learning of IPA at MIN Kota Yogyakarta II is categorized â€œpoorâ€. The similarity of the teaching implementation for both schools is they try hard to develop a democratic teaching and studentsâ€™ center-based teaching. They have a different teaching method. At SDN Tamansari 1 Kota Yogyakarta, the teachers implement minds-on and hands-on teaching process, that is, the experimental, demonstrational, and observational teaching, while the teachers at MIN Kota Yogyakarta implement theoretical (rote learning) teaching approach. Those differences were caused by some factors, such as: teachersâ€™ qualification, teachersâ€™ certification and professionalism, and the studentsâ€™ background.